In Vitro Technics for Determination of the Eye Irritant Properies of the Agrochemicals - Buda, István; Major, László; Szabó, Rita; Saidon, Nadhirah Binti; Lehel, József; Budai, Péter (GEORGIKON FOR AGRICULTURE, 2024)
Until now the most popular method to classify substances’ eye irritation potential is the OECD 405 test guideline. The basis of this is the Draize-test, which is one of the most criticized in vivo methods, because of the injuries of the test animals and subjective nature of the test in recording the results. Nowadays, several alternative tests are available which can be partly or totally replaced the in vivo eye irritation testing depending on the circumstances. The Isolated Chicken Eye Test (ICET) is part of these alternative methods. Four different agrochemicals (Biscaya, Dezormon, Kyleo, Pulsar 40 SL) were examined with this in vitro method. In ICET the eye irritation potential of test items were predicted based on the combination of three endpoints: corneal swelling, corneal opacity and fluorescein retention. The basis of determination of each endpoint was the differences between values of the base line measurement and values of any observation time points after the post-treatment rinse. Three agrochemicals showed different severity irritation potential and one agrochemical did not show any effect on the treated corneas. Comparing these in vitro results with the available in vivo data of the tested agrochemicals, results are found to be corresponding to each other.
Keywords: eye irritation; in vitro; corneal swelling; corneal opacity; fluorescein retention